ESTIMATING SUSTAINABLE EFFORT RATES FOR SKIPJACK TUNA FISHERIES LANDED AT YOGYAKARTA’S COASTAL FISHING PORT USING THE FOX MODEL - Suharyanto; Mustaruddin, Mustaruddin; Mantani, Sayuri; Nurlela, Eli; Barokah, Sinatria (Marine Fisheries : Journal of Marine Fisheries Technology and Management, 2025)
This study aims to estimate the fishing effort for skipjack tuna (Katsuwonus pelamis) landed at Sadeng Coastal Fishing Port, Yogyakarta, under three management conditions: Maximum Sustainable Yield (MSY), Maximum Economic Yield (MEY), and Open Access Equilibrium (OAE), using the Fox model. The Fox model includes a key variable that helps balance ecological sustainability with economic profitability, ensuring the long-term viability of both the fishery and the livelihoods it supports. The skipjack tuna assessed in this study were caught using purse seines in the Indian Ocean south of Yogyakarta. Catch and fishing trip data from 2015 to 2021 were analyzed using the Fox bioeconomic model, a development of the Gordon-Schaefer model. The research was conducted from March to May 2022. Under MSY conditions, the estimated catch (CMSY) was 493,012 kg with an effort (EMSY) of 170 trips per year, yielding an annual profit of IDR 4,768,675,442. Under MEY conditions, the estimated catch (CMEY) was 474,424 kg with an effort (EMEY) of 127 trips, resulting in a higher annual profit of IDR 5,071,245,038. Under OAE conditions, the estimated catch (COAE) was 337,761 kg with an effort (EOAE) of 363 trips per year. Based on the Fox model, the current fishing effort is at 70% of EMSY, indicating that the skipjack tuna fishery in this area is not overfished. Keywords: Bioeconomic, EMSY, purse seine,Sadeng, Indian Ocean